INTEGRATED MICROTREMOR AND GEOSPATIAL ANALYSIS FOR LIQUEFACTION POTENTIAL EVALUATION IN KAPANEWON PUNDONG - Maharani, Yohana Noradika; Nugroho, Arif Riyanto Budi; Paripurno, Eko Teguh; Suharsono, Suharsono; Mujianto, Mujianto (JOURNAL ONLINE OF PHYSICS, 2025)
Kapanewon Pundong is in an active tectonic zone and has experienced significant seismic events, including the 2006 Bantul earthquake (Mw 6.3), which caused extensive damage. Liquefaction was a key contributor to infrastructure failure during the event. This study aims to evaluate liquefaction potential in Kapanewon Pundong through integrated microtremor and geospatial analysis. The Horizontal-to-Vertical Spectral Ratio (HVSR) method assessed local site effects that influence ground shaking. Liquefaction probability was estimated using the model by Zhu et al. (2017), considering parameters such as Vₛ₃₀, PGV, water table depth (WTD), distance to water bodies (DW), and average annual precipitation. The research findings include Vₛ₃₀ values that range from 221 to 893 m/s, PGV values from 16 to 29 cm/s. Panjangrejo and Srihardono villages exhibit the highest liquefaction probabilities, up to 30%. The estimated Liquefaction Spatial Extent (LSE) in these areas reaches 5.1%. These findings identify high-risk zones for earthquake-induced liquefaction and provide a quantitative foundation for spatial planning and disaster mitigation strategies in the region.